Twelve-week physical exercise does not have a long-lasting effect on kynurenines in plasma of depressed patients - Millischer V (Dove Medical Press, 2017)
Vincent Millischer,1,2 Sophie Erhardt,3 Örjan Ekblom,4 Yvonne Forsell,5 Catharina Lavebratt1,2 1Department of Molecular Medicine and Surgery, Karolinska Institutet, 2Center for Molecular Medicine, Karolinska University Hospital, 3Department of Physiology and Pharmacology, Karolinska Institutet, 4Department of Sport Sciences, The Swedish School of Sport and Health Sciences, GIH, 5Department of Public Health Sciences, Karolinska Institutet, Stockholm, Sweden Background: Physical exercise has well-characterized positive effects on depressive symptoms. The underlying biologic mechanisms are, however, far from established. A recently discovered mechanism has linked the enhanced conversion of kynurenine to kynurenic acid (KYNA) to an increased resilience toward stress-induced depression in mice. The aim of this study was to translate these findings to humans.Materials and methods: Kynurenine and KYNA levels were measured by high-performance liquid chromatography in plasma samples from 117 patients affected by mild-to-moderate depression before and within a week after a 12-week training period at three different intensities. The patients were part of the Regassa study.Results: No differences in plasma levels of kynurenine and KYNA or in their ratio could be detected between before and after training. No effect of the intensity group could be observed. No correlation with the improvement in cardiovascular fitness (Åstrand score) or the improvement in mood (Montgomery Åsberg Depression Rating Scale score) could be observed.Limitations: As the Regassa study is based on an intention-to-treat protocol, the exact time and the exact intensity of the physical exercise are not known. Analyses of pulse data as well as personal interviews, however, were used to control the exercise protocols. Furthermore, the observations reflect chronic changes.Conclusion: Physical exercise positively affects mood and cardiovascular fitness, but does not lead to long-lasting changes in plasma levels of kynurenine and KYNA in patients affected by mild-to-moderate depression. Keywords: kynurenine pathway, kynurenine, kynurenic acid, depression, physical exercise